Multilevel analysis of discrimination of people living with HIV/AIDS and associated factors in Ghana: demographic health survey of 2022 Ghana data - Melkam, Mamaru; Fente, Bezawit Melak (Frontiers in Public Health, 2024)
The negative effects of stigma and discrimination in communities and families include medication non-adherence, heightened psychological distress, verbal and physical abuse, a lack of social support, isolation, and dangerous health behaviors such as hiding prescriptions.Because of this, those who are at risk of HIV infection or are unsure if they have it could choose not to get tested for the virus out of fear of stigma and a desire to maintain their privacy and secrecy regarding their status in medical settings. Despite the huge burden of HIV/AIDS discriminatory attitudes limited studies were conducted in Ghana. Therefore, this study provides the burden of discriminatory attitudes and its determinant factors of people who are living with HIV/AIDS in Ghana.Objective: to determine the prevalence of discriminatory attitudes and associated factors of people who are living with HIV/AIDS in Ghana from recent DHS data.Method: Secondary data analysis was used for this multilevel logistic regression analysis based on the Ghana Demographic Health Survey of 2022. Data extraction, cleaning, and analysis were conducted by using Stata version 14. The community of Ghana from the 15 to 49 age group was used for this study with a final sample size of 22,058 participants. Four separate models were fitted incorporating individual and community levels. Multilevel logistic regression models were calibrated to determine the associated factors at the individual and community level with discriminatory attitudes intimate partner violence with a 95% CI and AOR.The prevalence of discriminatory attitudes towards people living with HIV ADISAIDS was 60.92% with a 95% CI (60.13,61.70) among Ghana DHS. The associated factors for this study were Lower wealth status, having no compressive comprehensive knowledge of HIV, low educational status at the individual level, and low wealth status at the community level,.